2010
DOI: 10.2174/1874192401004010117
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fluorodeoxyglucose Uptake Following Endovascular Abdominal Aortic Aneurysm Repair: A Predictor of Endoleak?

Abstract: The main criterion for abdominal aortic aneurysm (AAA) repair is an AAA diameter ≥5.5 cm. However, some AAAs rupture when they are smaller. Size alone may therefore not be a sufficient criterion to determine rupture risk. Fluorodeoxyglucose (FDG) uptake is increased in the presence of inflammation and it was suggested that this may be a better predictor of rupture risk than AAA size. Furthermore, increased FDG uptake following endovascular AAA repair may be an indirect predictor of continuous AAA sac enlargeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A diameter of ≥ 5.5 cm is the main criterion for abdominal aortic aneurysm repair. Increased FDG uptake in the presence of inflammation was suggested that this may be a better predictor of rupture risk than aneurysm size (10). In a prospective study by Keidar Z et al (11), a total of 39 patients with 69 grafts (range 1-4 grafts/patient) were evaluated using FDG-PET/CT.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…A diameter of ≥ 5.5 cm is the main criterion for abdominal aortic aneurysm repair. Increased FDG uptake in the presence of inflammation was suggested that this may be a better predictor of rupture risk than aneurysm size (10). In a prospective study by Keidar Z et al (11), a total of 39 patients with 69 grafts (range 1-4 grafts/patient) were evaluated using FDG-PET/CT.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…42 Therefore, the role of 18-FDG needs to be investigated further in the post-EVAR course, in order to delineate its potential role as a predictor of endoleaks. 42,43 …”
Section: Association Of Biomarkers With Hemodynamic Changesmentioning
confidence: 99%
“…7 Increased FDG uptake involving the aortic wall, resulting from inflammation, has been suggested to be a predictor for an endoleak and AAA rupture risk. 8 Recently, early, dynamic PET/CT and PET angiography for endoleak detection after EVAR has been proposed 9 although is only likely to find utility if intravenous contrast is contraindicated. Given the increasing use of endovascular techniques for the repair of AAA, with their associated endoleaks, the recognition of delayed endoleaks, outside of routine CT surveillance programmes, on PET/CT scans performed for other indications is of critical importance.…”
mentioning
confidence: 99%